The Relationship Between Emotion Regulation and Psychological Well-Being Among Psychology Student at University X - Pasai Yu’la Arsydna; Anggraini Cindi; Rasmi I Gusti Ayu Andhika Sonia; Sovitriana Rilla (Siber Nusantara Research Publisher, 2026)
Psychology students face heightened psychological demands owing to the dual expectation that they possess the capacity to manage their own emotions while simultaneously being equipped to assist others with emotional difficulties. When not accompanied by adequate emotion self-regulation skills, such conditions may adversely affect students' psychological well-being. This study aimed to examine the relationship between emotion regulation and psychological well-being among psychology students. A total of 38 participants were recruited using purposive sampling. Emotion regulation was measured using the Emotion Regulation Questionnaire (ERQ; Gross & John, 2003), and psychological well-being was assessed using Ryff's Psychological Well-Being Scale. Data were analysed using Spearman rank-order correlation, following normality assumption testing. A statistically significant positive correlation was found between emotion regulation and psychological well-being (r = 0.395, p = .014), indicating that individuals with stronger emotion regulation capacity tend to exhibit higher levels of psychological well-being. These findings underscore the importance of fostering effective emotion regulation strategies among psychology students as a means of enhancing their psychological well-being.